Comparison of anaesthesia 'Day 1 skills' expectations between veterinary anaesthetists and general practitioners. (28th February 2015) - Duncan, J. C.; Ross, M.; Rhind, S.; Clutton, E.; Shaw, D. J.
Abstract : Day One Skills (DOS) were introduced by the Royal College of Veterinary Surgeons (RCVS) in 2006 as a guideline for minimum skills required by a veterinary graduate. However, the RCVS anaesthesia DOS are broad and do not specify differences in skills required for different species. The aims of this study were: (1) to determine which anaesthesia skills were considered essential for day one practice by UK‐based veterinary practitioners (GPs) and anaesthetists; and (2) to explore current opinions on veterinary undergraduate anaesthesia training. Questionnaires for veterinary GPs (QGP s) and veterinary anaesthetists (QVA s) were developed which asked general information on expectations of anaesthesia skills as well as specific expectations for the common veterinary species. Fifty‐five UK‐based members of the Association of Veterinary Anaesthetists responded, with a random sample of veterinary practices stratified by UK county generating 234 responses and a convenience sample targeted at more specialist veterinary specialities in the UK generating 161 responses. There was close overall agreement between the two groups of GPs and anaesthetists on essential anaesthesia DOS. However, expectations varied with species—greatest in cats and dogs, lowest in exotics. Many respondents commented that new veterinary graduates lack practical skills and should not be expected to be omnicompetent across all species. In conclusion, anaesthesia undergraduate training should prioritise essential practical DOS.